p.His16Arg of STXBP1 (MUNC18-1) Associated With Syntaxin 3B Causes Autosomal Dominant Congenital Nystagmus - Li, Yulei; Jiang, Lei; Wang, Lejin; Wang, Cheng; Liu, Chunjie; Guo, Anyuan; Liu, Mugen; Zhang, Luoying; Ma, Cong; Zhang, Xianqin; Gao, Shangbang; Liu, Jing Yu (Frontiers in Cell and Developmental Biology, 2020)
Congenital nystagmus (CN) is an ocular movement disorder manifested as involuntary conjugated binocular oscillation and usually occurs in early infancy. The pathological mechanism underlying CN is still poorly understood. We mapped a novel genetic locus 9q33.1-q34.2 in a larger Chinese family with autosomal dominant CN and identified a variant (c.47A>G/p.His16Arg) of STXBP1 by exome sequencing, which fully co-segregated with the nystagmus phenotype in this family and was absent in 571 healthy unrelated individuals. The STXBP1 encodes syntaxin binding protein 1 (also known as MUNC18-1), which plays a pivotal role in neurotransmitter release. In unc-18 (nematode homologue of MUNC18-1) null Caenorhabditis elegans, we found that the p.His16Arg exhibits a compromised ability to rescue the locomotion defect and aldicarb sensitivity, indicating a functional defect in neurotransmitter release. In addition, we also found an enhanced binding of the p.His16Arg mutant to syntaxin 3B, which is a homologue of syntaxin 1A and specifically located in retinal ribbon synapses. We hypothesize that the variant p.His16Arg of STXBP1 is likely to affect neurotransmitter release in the retina, which may be the underlying etiology of CN in this family. Our results provide a new perspective on understanding the molecular mechanism of CN.